The implementation of the Continuous Progression Scheme in the Camiling West-San Clemente School District, Division of Tarlac - Neri, Venancio F. 1923-
The respondents were 6 division supervisors, one district supervisor, 8 elementary school principals, 50 male and 50 female teachers and 80 male and 80 female grade 5 and 6 pupils selected at random. The Continuous Progression Scheme (CPS) is a plan of promotion which provides the child the opportunity to attain the highest degree or point of growth and progress at his own rate from grade to grade. The division and district supervisors and the principals conducted workshops, seminars, conferences, and other inservice training activities on the scheme, encourages teachers to read articles on the CPS, and invited parents to visit classrooms to see for themselves how the CPS was actually implemented. Implementation had no definite direction and teachers used instructional materials and strategies in traditional manner. Pupils had uncertain opinions about the CPS.